Analysis of Risk of Burn Out at Workers in the Field ff Social Services and Health Care - Budayová, Zuzana; Ludvigh Cintulová, Lucia; Mrosková, Lenka (Journal of Education Culture and Society, 2023)
Aim. The aim of the research was to analyse the burnout rate of these social workers and nurses, as well as to determine the relationship between burnout syndrome and other important factors, including lifestyle, stress, resistance to stress and other selected demographic indicators.Methods. The Maslach Burnout Inventory was used to collect burnout data in 2021 during the second wave of the Covid-19 pandemic. The research sample consisted of 623 women aged 35-55 who work in social services facilities for the elderly and nurses working in the geriatrics department at a hospital in the western part of Slovakia.Results. Research has shown that lifestyle has a significant impact on the development of burnout syndrome in connection with the quality of work and personal relationships, which can help eliminate feelings of frustration, exhaustion and personal failure in the workplace. Burnout affects social workers regardless of age and education, but with older age and length of practice in the same facility, the risk of manifestations of burnout increases. Significant differences in burnout rates between social workers and nurses in the individual dimensions of exhaustion, depersonalisation and professional attitudes were confirmed. High levels of exhaustion have even shown an increased risk of alcohol consumption among these workers.Conclusion. The development of chronic stress in health care workers can put them at risk of burnout, which is characterized by emotional exhaustion (EE), depersonalization (DP) in interactions with patients and social clients, and low levels of personal accomplishment (PA) in social work and health care.